Regulation of Cytokine Production by γδ T Cells - Wesch, Daniela; Marischen, Lothar; Kabelitz, Dieter (Current Medicinal Chemistry - Anti-Inflammatory & Anti-Allergy Agents, 2005)
A minority of peripheral blood T lymphocytes used heterodimeric T cell receptor (TCR) composed of a Vγ9 chain associated with Vδ2. These circulating Vγ9Vδ2 γδ T cells mainly recognize low-molecular-mass non-peptide antigens derived from microbes and plants in a MHC-unrestricted manner. Furthermore, they produce rapidly after antigen contact cytotoxic molecules and cytokines, thereby activating innate immune cells, facilitating adaptive immune responses of αβ T cells, protecting the host against infections with certain microbial pathogens, and playing a role in tumor defense. Another γδ T cell subset underrepresented in the peripheral blood expresses Vd1 chain associated with variable Vg elements and comprises the major γδ T cell population in epithelial tissues such as the small intestine. Homologous γδ T cells are found in the mouse in vagina, uterus, lung and skin. Vδ1 γδ T cells mainly recognize antigens restricted to certain cell types of epithelial origin, which are induced upon stress, infection, inflammation and tumor growth, and thus play a role in immunosurveillance against malignancy, pathogen eradication, and wound healing. Several reports suggest that γδ T cells are immunregulatory cells, interacting and modulating the activity of other immune cells directly or by cytokine production. Here we summarize the current knowledge on the role of cytokines produced by γδ T cells and their ability to influence and regulate other cells of the immune system.
Keywords: pregnancy